Peripheral Dose Measurement for 6 MV Photon Beam - Nur Iziana Mohsin; Ahmad Zakaria; Reduan Abdullah; Mun Fei Wong (Journal of Medical Physics and Biophysics, 2014)
The objective of this study is to measure the peripheral dose (PD) at different depths and field sizes using film dosimetry. PD of 6 MV Siemens Primus linear accelerator photon beam for 10 cm square field and 2.5 cm diameter cone were measured at 1.5 cm and 10 cm depth, 100 cm source surface distance (SSD) with Kodak EDR2 film. PD for 10 cm square field and 2.5 cm cone were measured for the distance 1 cm to 5 cm from the geometric field edge. PD was calculated as a percentage of the central axis dose. The PD for both field sizes decreased with increasing distance from the beam edge. PD was also larger for 10 cm square field compared to 2.5 cm circular field for both depths. At 10 cm depth, the measured PD was 20% and 10% higher compared to that of 1.5 cm depth for 10 cm and 2.5 cm field size respectively. The PD for a given beam energy is a function of distance from the beam edge, field size and depth. At any depth measured, PD increases as the field size increases due to radiation scattered from the beam and scatter arising from within the medium. At deeper depth, more Compton electrons are produced and scattered to the peripheral region hence causes the PD to increase with depth. At any field size measured, peripheral dose increases as the depth increases. PD also increases as the field size increases.